Antibacterial activity and mechanism of flavonoids from Chimonanthus salicifolius S. Y. Hu. and its transcriptome analysis against Staphylococcus aureus - Zhou, Huan; Chen, Lingli; Ouyang, Kehui; Zhang, Qingfeng; Wang, Wenjun (Frontiers in Microbiology, 2023)
This work aims to explore the antibacterial activity and underlying mechanisms of flavonoids from Chimonanthus salicifolius S. Y. Hu. (FCS) with a purity of 84.2 ± 2.0%. The results showed that FCS has potential effects on tested strains with the maximum diameter of inhibition zone (DIZ) was 15.93 ± 2.63 mm, the lowest minimum inhibition concentration (MIC) was 1.56 mg/mL and the lowest minimum bactericide concentration (MBC) was 6.25 mg/mL. In addition, the bacterial growth curve test, release of extracellular alkaline phosphatase (AKP), loss of intracellular components, DNA damage and transmission electron microscope (TEM) suggested that FCS could destroy the cell wall and membrane, cause the loss of intracellular substance, cause DNA damage and even lead to cell death. Moreover, the antibacterial mechanism of FCS against Staphylococcus aureus (S. aureus, Gram-positive bacteria) was further confirmed by the transcriptome analysis and quantitative RT-PCR at the molecular level for the first time. A total of 671 differentially expressed genes (DEGs) were identified after treated with FCS (1/2 MIC), with 338 and 333 genes showing up-regulation and down-regulation, respectively. The highlighted changes were those related to the biosynthesis of bacteria wall and membrane, DNA replication and repair, and energy metabolism. Overall, our research provides theoretical guidance for the application of FCS, which is expected to be potentially used as a natural antimicrobial agent in food safety.